Are They on Target? The Order of Thinking Skills of the Reading Comprehension Questions and Tasks of the Merdeka Curriculum English Textbook for Indonesian High School - Kamil, Dairabi; Aswad, Muhammad; Hidayat, Marzul; Fortunasari, Fortunasari (Universitas Jambi, Indonesia, 2024)
This study sought to investigate the order of thinking of the reading comprehension questions and tasks of the English textbook for Grade 10 of Indonesian high school. The textbook was written within the framework of the Merdeka Curriculum to promote Higher Order of Thinking (HOTS) and was launched by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia in 2022. Drawing on a Quantitative Content Analysis design by using the Revised Bloom’s Taxonomy as a reference for identification of HOTS, the present study analyzed 50 reading questions and tasks of the textbook. The results showed that the majority of the questions and tasks focused on remembering and evaluating the texts and required the reader to recall and comprehend the information that mostly belonged to the category of Lower Order of Thinking (LOTS). There were only few questions and tasks that required the readers to analyze and create based on the information from the text. To some extent, these showed a misalignment between what the Merdeka Curriculum seeks to promote in terms of HOTS and what the textbook realizes.